1995
DOI: 10.1111/j.1476-5381.1995.tb15908.x
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin‐ and cyclopiazonic acid‐induced endothelium‐dependent hyperpolarization in rat mesenteric artery

Abstract: 1 The present study was designed to determine whether putative, selective inhibitors of the Ca2+-pump ATPase of endoplasmic reticulum, thapsigargin (TSG) and cyclopiazonic acid (CPA), induce endothelium-dependent hyperpolarization in the rat isolated mesenteric artery. The membrane potentials of smooth muscle cells of main superior mesenteric arteries were measured by the microelectrode technique. 2 In tissues with endothelium, TSG (10--10-S M) caused sustained hyperpolarization in a concentration-dependent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
37
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 43 publications
13
37
0
1
Order By: Relevance
“…This interpretation is consistent with the recent finding that a thapsigargin-insensitive Ca 2ϩ pool is present in a subcompartment of the endoplasmic reticulum in different mammalian cells (29). In addition, the presence of SERCA2a and SERCA2b in the endothelium layer of small mesenteric arteries found in the present study is consistent with previously reported endothelium-dependent relaxation elicited by SERCA inhibitors in these vessels (11).…”
Section: Discussionsupporting
confidence: 83%
“…This interpretation is consistent with the recent finding that a thapsigargin-insensitive Ca 2ϩ pool is present in a subcompartment of the endoplasmic reticulum in different mammalian cells (29). In addition, the presence of SERCA2a and SERCA2b in the endothelium layer of small mesenteric arteries found in the present study is consistent with previously reported endothelium-dependent relaxation elicited by SERCA inhibitors in these vessels (11).…”
Section: Discussionsupporting
confidence: 83%
“…After blockade of both NO and PGI 2 synthesis, we tested the effects of charybdotoxin plus apamin on basal perfusion pressure and acute hypoxic vasoconstriction. Thapsigargin (TG) caused NO- and PGI 2 -independent vasodilation, consistent with previous reports [11, 38, 39]. We examined the effect of charybdotoxin plus apamin on the vasodilation induced by TG.…”
Section: Introductionsupporting
confidence: 69%
“…Thus, the Ca 2 influx during rest was completely buffered by the SR. Although the membrane depolarizing effects of CPA, thapsigargin or ryanodine were reported in the rat pressurized posterior cerebral artery (25) and rat carotid artery (18), such effects were not observed in rat large and small mesenteric arteries (26,27). Based on these observations, we believe that CPA, thapsigargin and ryanodine induced a large contraction in the SHR resistance artery by compromising the Ca channel activity was also reported in small mesenteric arteries from Dahl salt-sensitive rats (32).…”
Section: Discussionmentioning
confidence: 75%